Experimental Approaches to Student Success - Tim Messner (EXARC Journal)
An undergraduate student who hopes to secure meaningful work or pursue graduate studies needs to have excellent grades. This is true for all disciplines, but especially for niche fields like archaeology. Grades alone, however, are rarely enough. Employers and graduate schools seek candidates that are not only ‘book smart’ but who have life experiences that cultivate strength, perspective and perseverance. Thus, the undergraduate student who is looking beyond graduation must strive to gain these experiences and differentiate themselves from their peers.